Ukraina w myśli politycznej Jerzego Giedroycia - Marszał, Maciej; Srokosz, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The paper presents views of Jerzy Giedroyc editor-in-chief of “Kultura” most influential Polish-émigré literary-political journal after 1945 on the issue of Poland-Ukraine relations. From the very onset of “Kultura” in 1947 Giedroyc strongly advocates dialogue between Poland and Ukraine as a mean to achieve reconciliation between these nations. Recognition of Polish eastern border of 1945 as final, clarification of difficult past, support of Ukrainian drive to independence and wide cultural cooperation between two countries formed the pillar of his views. In Soviet times Gidroyc postulates the concept of federation between Poland, Ukraine, Lithuania and Belarus ULB. Its raison d’être was to guarantee independence from both Russia and Germany. After Ukraine’s independence in 1991 Giedroyc departed from the idea of federation and turn to advocate the alliance and close Polish-Ukrainian cooperation. Giedroyc seen the role of Poland as a main link between Ukraine and Western Europe and a supporter of Ukraine independence from Russia.
Keywords: Ukraina; Giedroyc, Jerzy (1906-2000); myśl polityczna